Construction of full-length infectious cDNA clones of apple chlorotic leaf spot virus and their agroinoculation to woody plants by a novel method of vacuum infiltration - Zhang, Lei; Jelkmann, Wilhelm (Plant disease, 2017)
Construction and agroinoculation of full-length infectious cDNA clones of plant RNA viruses have been used in plant virology to prove Koch’s postulates and for development of viruses as vectors for expressing foreign genes in plants. Four full-length cDNA clones (pIF3-12, pIF3-14, pIF3-15, and pIF3-19) of Apple chlorotic leaf spot virus (ACLSV) isolate 38/85 were produced. Two of the four full-length cDNA clones (pIF3-15 and pIF3-19) proved to be infectious on Nicotiana occidentalis 37B test plants by agroinoculation and were then mechanically transmissible to healthy N. occidentalis 37B. The genomic cDNAs of ACLSV pIF3-15 and pIF3-19 shared nucleotide identity of 77.5%, demonstrating mixed infections of multiple strains of ACLSV in the source tree of isolate 38/85. The two full-length cDNA clones were agroinoculated to apple seedlings by a newly developed vacuum infiltration method. The success rate of agroinoculation was greater than 78%, defined as the number of PCR positive seedlings to the number of apple seedlings that survived. ACLSV was transmissible from agroinoculated seedlings by cleft grafting. The results of this study will be useful for construction of infectious cDNA clones of plant viruses from full-length PCR fragments and agroinoculating woody host plants using the vacuum infiltration method outlined here.